2007
DOI: 10.1063/1.2756072
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz frequency bandpass filters

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
42
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 19 publications
1
42
0
4
Order By: Relevance
“…The technique is thus ideal for producing photonic devices that operate in the THz region of the electromagnetic spectrum. In recent work, we have shown how such devices can be used to filter THz radiation at normal incidence [16], and further theoretical developments of these ideas have considered waves that are obliquely incident on a prism structure of metallic pillars arranged on a hexagonal lattice [15]. The first two photonic bands of the basic hexagonal lattice system, with the electric field polarized parallel to the pillars' axis, are shown in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The technique is thus ideal for producing photonic devices that operate in the THz region of the electromagnetic spectrum. In recent work, we have shown how such devices can be used to filter THz radiation at normal incidence [16], and further theoretical developments of these ideas have considered waves that are obliquely incident on a prism structure of metallic pillars arranged on a hexagonal lattice [15]. The first two photonic bands of the basic hexagonal lattice system, with the electric field polarized parallel to the pillars' axis, are shown in Fig.…”
mentioning
confidence: 99%
“…The inclusion of a loss term has the additional effect of reducing the value of f J by a few percent. Details of the basic fabrication methods employed have been published elsewhere [16], but in brief, high-aspect-ratio polymer pillars are formed by backside UV exposure of SU-8 50 on a glass substrate, before being sputtered with gold. Because the gold thickness is greater than the electromagnetic radiation skin depth, the pillars behave in effect like solid metallic rods.…”
mentioning
confidence: 99%
“…They showed that the effective plasma frequency is a function of the array geometry and is independent of the bulk plasma frequency of the metal. However, to produce an effective plasma frequency in the THz regime, the rods need to be of the order of tens of microns diameter and of sufficient length to fully confine the incident beam [10]. This 'microbrush' type of structure is difficult and expensive to fabricate using manual assembly type techniques.…”
Section: High Aspect Ratio Metal Rod Based Thz Filtersmentioning
confidence: 99%
“…2 shows an overview of the process flow used to fabricate arrays of microrods. The details of the fabrication process can be found in [10]. The key novelty is the use of backside UV exposure of SU8-50 which can produce structures with diameters as small as 30 µm and heights in excess of 1.5 mm.…”
Section: High Aspect Ratio Metal Rod Based Thz Filtersmentioning
confidence: 99%
See 1 more Smart Citation